2019
DOI: 10.1002/ange.201900386
|View full text |Cite
|
Sign up to set email alerts
|

Resonance‐Mediated Below‐Threshold Delayed Photoemission and Non‐Franck–Condon Photodissociation of Cold Oxyallyl Anions

Abstract: The photoexcitation of cold oxyallyl anions was studied belowt he adiabatic detachment threshold at ap hoton energy of 1.60 eV.Photodetachment was observed through two product channels,delayed electron emission from along-lived anionic state and dissociative photodetachment via absorption of as econd photon. The former produced stable neutral C 3 H 4 O, while the latter resulted in the concerted elimination of CO + C 2 H 4 products.T he neutral oxyallyl singlet state has ab arrier-free route to cyclopropanone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…33,34 Moreover, electrostatic trapping of ionic products allows the identification and characterization of metastable intermediates and their decay mechanisms. 35,36 For example, in many cluster systems delayed fragmentation and delayed detachment were observed to occur long after the photoexcitation event and exhibit intricate competition with relaxation by black-body radiation as well as by exotic recurrent fluorescence mechanisms. 11,14,35,37,38 Advances in merged cation-anion beams make it possible to study the interactions of oppositely charged ionic species at low collision energies.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Moreover, electrostatic trapping of ionic products allows the identification and characterization of metastable intermediates and their decay mechanisms. 35,36 For example, in many cluster systems delayed fragmentation and delayed detachment were observed to occur long after the photoexcitation event and exhibit intricate competition with relaxation by black-body radiation as well as by exotic recurrent fluorescence mechanisms. 11,14,35,37,38 Advances in merged cation-anion beams make it possible to study the interactions of oppositely charged ionic species at low collision energies.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical requirement for whether a molecule can support a DBS is if |μ| > 1.625 D, although experiments have suggested that the condition is closer to |μ| > 2.0 D due to molecular rotation and centrifugal effects. Despite the DBS lying only 10–100 meV below the detachment threshold, , it has important roles in interstellar anion formation, electron transfer processes in biology, , and coupling of solute molecules with solvated electrons . Recent studies have suggested that DBSs are important in certain isomerization and dissociation reactions. , Underpinning each of these examples are the efficient nonadiabatic couplings that funnel population between the valence-localized and dipole-bound states and interactions with the electronic continuum.…”
mentioning
confidence: 99%
“…12 Recent studies have suggested that DBSs are important in certain isomerization and dissociation reactions. 13,14 Underpinning each of these examples are the efficient nonadiabatic couplings that funnel population between the valence-localized and dipole-bound states and interactions with the electronic continuum.…”
mentioning
confidence: 99%